KENDALA DALAM PEMBELAJARAN DARING BAGI SISWA PADA MATA PELAJARAN GEOGRAFI DI SMA NEGERI 16 SEMARANG (Edu Geography, 2022)
This study aims to determine the obstacles experienced by students during online learning activities in geography subjects at SMA Negeri 16 Semarang. The population in this study was the social studies class at SMA Negeri 16 Semarang. The sample of this research is class XI IPS 1 with 36 students taken using cluster random sampling technique. Methods of data collection using a questionnaire or questionnaire. The data analysis technique used descriptive statistics. Based on the result of this study, it was found that: online learning activities showed a percentage value of 86% in the poor category. After being researched, it turns out that there are obstacles in digital literacy activities, discussions, evalutions, and learning facilities. Therefore, it can be concluded that online learning activities are not running optimally.